Electric field‐revealed precursor ferroelectric properties of low lithium ion‐doped KTaO3. Issue 6 (2nd February 2016) - Trybuła, Zbigniew; Miga, Seweryn; Łoś, Szymon; Trybuła, Małgorzata; Dec, Jan
Abstract : The results of low‐temperature linear χ 1 ′ as well as nonlinear χ 2 ′ and χ 3 ′ electric susceptibility and polarization P measurements of the K1– x Li x TaO3, x  = 0.01 crystal are presented. A coexistence of two different phases within a temperature range where the glassy state sets in is proposed. In the current work, we have proved the existence of an electric field‐revealed precursor ferroelectric phase without low‐frequency relaxation. With decreasing temperature, the second‐order nonlinear electric susceptibility, χ 2 ′, which is proportional to the polarization P, increases from zero at about 40 K to χ 2 ′ = 1.25 × 10 − 4 m · V − 1 at 4.2 K. This behavior is independent of the frequency of the ac probing electric field, and thus discloses the existence of a newly observed polarization component.